Turning a blind eye: the mobilization of radiology services in resource-poor regions - Jason Andrews; Schwarz Ryan; Maru Duncan; Basu Sanjay; Sharma Aditya; Moore Christopher (Globalization and Health, 2010)
Abstract While primary care, obstetrical, and surgical services have started to expand in the world's poorest regions, there is only sparse literature on the essential support systems that are required to make these operations function. Diagnostic imaging is critical to effective rural healthcare delivery, yet it has been severely neglected by the academic, public, and private sectors. Currently, a large portion of the world's population lacks access to any form of diagnostic imaging. In this paper we argue that two primary imaging modalities--diagnostic ultrasound and X-Ray--are ideal for rural healthcare services and should be scaled-up in a rapid and standardized manner. Such machines, if designed for resource-poor settings, should a) be robust in harsh environmental conditions, b) function reliably in environments with unstable electricity, c) minimize radiation dangers to staff and patients, d) be operable by non-specialist providers, and e) produce high-quality images required for accurate diagnosis. Few manufacturers are producing ultrasound and X-Ray machines that meet the specifications needed for rural healthcare delivery in resource-poor regions. A coordinated effort is required to create demand sufficient for manufacturers to produce the desired machines and to ensure that the programs operating them are safe, effective, and financially feasible.